RENOVATION OF RIVERSIDE SPACE FROM INDUSTRIAL PAST TO SUSTAINABLE FUTURE - Самойленко, Евгения (SWorldJournal, 2020)
Summary. Ukrainian cities are on the stage of industrial development, some of them have just started the process of transformation into post-industrial sustainable city. Majority of Ukrainian cities are stagnating. Ukrainian urban areas also have a parti